Assessment of early and post COVID-19 vaccination antibody response in healthcare workers: a multicentre cross-sectional study on inactivated, mRNA and vector-based vaccines. (5th January 2023) - Mansour Ghanaie, Roxana; Jamee, Mahnaz; Khodaei, Hannan; Shirvani, Armin; Amirali, Arezu; Karimi, Abdollah; Fallah, Fatemeh; Azimi, Leila; Armin, Shahnaz; Fahimzad, Seyed Alireza; Rafiei Tabatabaei, Sedigheh; Gholinegad, Zari; et al.
Abstract: In this multicentre study, we compared the status of antibody production in healthcare personnel (HCP) before and after vaccination using different brands of COVID-19 vaccines between March 2021 and September 2021. Out of a total of 962 HCP enrolled in our study, the antibody against the S1 domain of SARS-CoV-2 was detected in 48.3%, 95.5% and 96.2% of them before, after the first and the second doses of the vaccines, respectively. Our results showed post-vaccination infection in 3.7% and 5.9% of the individuals after the first and second doses of vaccines, respectively. The infection was significantly lower in HCP who presented higher antibody titres before the vaccination. Although types of vaccines did not show a significant difference in the infection rate, a lower infection rate was recorded for AstraZeneca after the second vaccination course. This rate was equal among individuals receiving a second dose of Sinopharm and Sputnik. Vaccine-related side effects were more frequent among AstraZeneca recipients after the first dose and among Sputnik recipients after the second dose. In conclusion, our results showed diversity among different brands of COVID-19 vaccines; however, it seems that two doses of the vaccines could induce an antibody response in most of HCP. The induced immunity could persist for 3–5 months after the second vaccination course.